INTERROGATING IRRESPONSIBLE DRIVING S v Scholtz 2006 1 SACR 442 (E) - Shannon Hoctor (Obiter, 2022)
The defence of non-pathological incapacity has been in something of a state of flux in the wake of the Supreme Court of Appeal’s decision in S v Eadie (2002 1 SACR 663 (SCA)). This defence again came under the spotlight in the case of Scholtz, in the context of a slew of charges arising out of the senseless drunken destruction perpetrated as a result of the driving of the appellant.